Critical transmission sectors in embodied atmospheric mercury emission network in China. (26th July 2021) - He, Kehan; Mi, Zhifu; Chen, Long; Coffman, D'Maris; Liang, Sai
Abstract: Atmospheric mercury is a crucial pollutant that must be well‐controlled to avoid damaging public health. It is thus necessary to understand from multiple perspectives the roles played by different industrial sectors, as well as their geographical distribution. Existing studies have overlooked the transmission sectors in the economic supply chains of the embodied atmospheric mercury emission network. In this paper, we offer a betweenness‐based account (BBA) for Chinese regions and industrial sectors in transmitting embodied atmospheric mercury emissions and in doing so have identified the transmitting hubs. Our results show that the Henan province acts as the transmission hub of the embodied atmospheric mercury emission network in China. The metallurgy, chemical, and construction industries generally play important roles in the transmission of embodied atmospheric mercury emissions across China. Henan's metallurgy sector, the third highest of all, is more closely linked with inter‐provincial sectors than the top two transmission sectors (the metallurgy industry of Jiangsu and the chemical industry of Shandong). This study can help policy makers improve mercury control measures by focusing on transmission processes for effective and comprehensive atmospheric mercury emission control.